Features of the japanese national team at the rugby World Cup 2019 in Japan - Shimozono, H.; Sasaki, K.; Yamamoto, T.; Watanabe, I.; Murakami, J. (13th World Congress of Performance Analysis of Sport and 13th International Symposium on Computer Science in Sport. IACSS&ISPAS 2022, 2023)
The Japanese national rugby team cleared all the preliminary leagues with a clean sweep and advanced into the final of the 2019 Rugby World Cup hosted in Japan. We examined the characteristics of this team in the ninth World Cup, which had been eliminated from the previous eight World Cups by losing in the preliminary rounds. The Japanese national team at the Rugby World Cup 2019 in Japan, was characterized by an increase in "international match experience," which allowed the team to approach the games with a different mindset than in the previous eight tournaments. In addition, compared to the teams that were eliminated from the preliminary league, Japan`s national team had been attacking in its strengths. By gaining more experience in international matches, it is believed that the Japanese national team established a method to demonstrate its strengths and implemented it at the World Cup.